2019
DOI: 10.1513/annalsats.201809-594oc
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Phenome-Wide Association Studies of Red Cell Distribution Width Identifies Key Associations with Pulmonary Hypertension

Abstract: Rationale: Red cell distribution width (RDW) is a prognostic factor in many diseases; however, its clinical utility remains limited because the relative value of RDW as a biomarker across disease states has not been established.Objectives: To establish an unbiased RDW disease hierarchy to guide the clinical use of RDW and to assess its relationship to cardiovascular hemodynamic and structural parameters.Methods: We performed phenome-wide association studies for RDW in discovery and replication cohorts derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…https://doi.org/10.1183/13993003.01486-2019 associated with RDW with a similar effect size (OR 2.0, 95% CI 1.75-2.4 per % increase in RDW) [7]. Our MR analysis was adequately powered to detect a causal role for RDW with an effect of this magnitude.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…https://doi.org/10.1183/13993003.01486-2019 associated with RDW with a similar effect size (OR 2.0, 95% CI 1.75-2.4 per % increase in RDW) [7]. Our MR analysis was adequately powered to detect a causal role for RDW with an effect of this magnitude.…”
Section: Discussionmentioning
confidence: 66%
“…We and others have demonstrated that one factor strongly correlated with survival in PAH is red cell distribution width (RDW) [5,6]. A recent hypothesis-free phenome-wide analysis indicated PAH, among several disease descriptors, as the most strongly associated with RDW (OR 2.0, 95% CI 1.75-2.4 per % increase in RDW) in a hospital population [7]. RDW (a measure of red blood cell (RBC) size variability in an individual) is part of the full blood count in standard hospital practice and readily available as a biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Thayer et al recently found that RDW portends poor outcomes for non-anemic PAH patients. 9 The value of RDW as a biomarker for multiple cardiovascular diseases has long been suggested, 44,45 but the pathophysiology involved has not been fully elucidated. Interestingly, our PAH rat model developed a non-anemic macrocytic red blood cell phenotype, with increased immature red blood cell production resulting in an increase in RDW.…”
Section: Discussionmentioning
confidence: 99%
“…Phecodes are aggregated ICD-9 codes that condense similar disease entities into one code, reducing the number of phenotypes from over 14,000 separate ICD-9 codes to 1,645 phecode groups, and have been utilized in multiple EHR and genetic studies. (38)(39)(40)(41)(42)(43)(44) We also conducted genetic analyses using COPD-associated…”
Section: Applications Of Phenotyping Algorithmmentioning
confidence: 99%
“…We also compared the frequency of phecodes across the two groups. (38)(39)(40)(41)(42)(43)(44) In COPD cases, the most frequent phecodes were chronic airway obstruction (100%), hypertension (77.1%), other symptoms of respiratory system (75.4%), essential hypertension (75.4%), and tobacco use disorder (63.0%).…”
Section: Clinical and Genetic Analyses Using A Phenotyping Algorithmmentioning
confidence: 99%